2022
DOI: 10.1002/mp.15699
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Monte Carlo 131I radiopharmaceutical dosimetry workflow using a 3D‐printed anthropomorphic head and neck phantom

Abstract: Purpose Approximately 50% of head and neck cancer (HNC) patients will experience loco‐regional disease recurrence following initial courses of therapy. Retreatment with external beam radiotherapy (EBRT) is technically challenging and may be associated with a significant risk of irreversible damage to normal tissues. Radiopharmaceutical therapy (RPT) is a potential method to treat recurrent HNC in conjunction with EBRT. Phantoms are used to calibrate and add quantification to nuclear medicine images, and anthro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 81 publications
0
0
0
Order By: Relevance
“…Good agreement was shown between the SPECT/CT image-based workflow and the measured TLD values; the largest difference was a 5.5% overestimation using the image-based workflow. In line with previous work ( Adam et al 2022 ), the necessity of PVC is required for accurate measurements of activity and subsequently the calculated absorbed dose distribution. Without PVC, the activity in the sphere was underestimated by 49.5% in the SPECT images.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Good agreement was shown between the SPECT/CT image-based workflow and the measured TLD values; the largest difference was a 5.5% overestimation using the image-based workflow. In line with previous work ( Adam et al 2022 ), the necessity of PVC is required for accurate measurements of activity and subsequently the calculated absorbed dose distribution. Without PVC, the activity in the sphere was underestimated by 49.5% in the SPECT images.…”
Section: Discussionsupporting
confidence: 59%
“…All differences were within calculated uncertainties in the activity concentration (23.6% uncertainty) for a 16 ml sphere. ( Adam et al 2022 ). These uncertainties are of similar magnitude to those reported by Gregory et al , where they reported an uncertainty in the activity determination to be 16% for a 5 cm sphere ( Gregory et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations